SAT0522 Efficacy and Safety of Ultrasonographic Guided Percutaneous Needle Planter Fasciotomy as A Treatment for Chronic Planter Fasciitis. (15th July 2016) - Mortada, M.; Sharaf, D.M.; Hammad, M.A.H.; Ezzeldin, N.
Abstract : Background: Plantar fasciitis (PF) is the most common cause of heel pain. Approximately 10% of the cases develop recalcitrant symptoms and are offered various forms of surgical intervention. Ultrasound guided needle planter fasciotomy is a minimal invasive method that may help this group of patients (1). Objectives: To assess the efficacy and safety of ultrasonographic guided percutaneous needle planter fasciotomy as a treatment for chronic planter fasciitis. Methods: ultrasound guided planter fasciotomy (1) was carried out in one hundred and seven patients who had chronic planter fasciitis that did not respond to conservative treatment including medical treatment, physiotherapy and local corticosteroid injection. Following induction of local anesthesia, a 14-gauge needle was guided toward and into the plantar fascia by real-time sonography.Visual analogue scale (VAS) for heel pain and ultrasonographic character of planter fascia (thickness and echogenicity) were assessed on the initial (W0), 2 weeks later (W2) and 6 months after treatment (W24). Results: A highly significant difference was found between VAS and sonographic findings before and after fasciotomy. Patients improved significantly at 2 weeks compared to baseline and also at 6 months compared to baseline and 2 weeks (table 1 ). Nighty seven (90.7%) of patients stated that "the procedure had been worthwhile". There were no complications during or following needle fasciotomy. Conclusions: Ultrasonographic guided percutaneous needle planter fasciotomy is a safe and an effective method in patients with chronic planter fasciitis who did not respond to conservative treatments including local corticosteroid injections. References: Folman et al, Foot and Ankle Surgery 11 (2005) 211–214 Disclosure of Interest: None declared